The Use of an Integrative Approach in Teaching Foreign Languages in the Process of Distance Learning - Urinboeva Khayotkhon Makhamadinovna (International Journal on Integrated Education, 2021)
The article deals with the issues based on the use of an integrative approach in teaching foreign languages. The reader's attention is drawn to the classification of types of distance educational technologies and special attention is paid to the most promising area of Internet technologies - electronic educational resources. An attempt is made to determine the features of the use of the integrative approach in the formation of foreign language communicative competence of students and to substantiate the levels of integration in the framework of teaching a foreign language. The author concludes about the possibilities and prospects of an integrative approach in order to improve the quality of language training in the process of distance learning.